DOCUMENTARY ANALYSIS IN NURSING THESES: DATA COLLECTION TECHNIQUES AND RESEARCH METHODS - Selma Regina de Andrade; Márcia Danieli Schmitt; Bruna Carla Storck; Talita Piccoli; Andriela Backes Ruoff (Cogitare enfermagem, 2018)
Objective: to characterize the use of documentary analysis in theses defended in the Postgraduate Programs in Nursing in Brazil. Method: bibliometric study undertaken in the Theses Database of the Coordination for the Improvement of Higher Education Personnel and on the Sucupira Platform, in January 2017. Of the 463 theses found, 95 met the study objective. They were organized and analyzed, between February and June 2017, using Microsoft Excel®, and contained the following items: Higher Education Institute; title, authors, year and supervisor; theoretical framework; type/nature of the study; document analyzed, complementary techniques/methods and use of documentary analysis. Results: documentary analysis is being used predominantly as a technique for collecting and analyzing data, complementing other techniques, and is applied little as a method. Of the theses, 61 (64.21%) had a qualitative design. Conclusion: documentary analysis makes it possible to formulate empirical evidence through examining documents elaborated by nurses, contributing to the strengthening of nursing as a profession.